Decolonizing brazilian philosophy: ethical and political challenges for philosophies of the global south - Gelamo, Rodrigo Pelloso [UNESP]; Garcia, Amanda Veloso; Rodrigues, Augusto [UNESP] (FapUNIFESP (SciELO), 2022)
The goal of this article is to problematize some of the main practices of Brazilian university philosophy, in order to denounce its colonizing assumptions and point out its limits to elaborate a philosophical thought capable of relating, effectively, with the problems that affect us in the Brazilian territory. We will analyze how the strategy of reading and explaining European and unitedstatian texts, predominantly considered the classic references to philosophy, operate the relations of knowledge and domination that exist between the global North under the peoples of the South that they colonized. We will use the constitutive experience of the degree in philosophy at the University of São Paulo as an example of the practices and assumptions of coloniality by which our academic philosophy is modeled. From the contributions of Lélia Gonzalez (1988), Ailton Krenak (2019), Silvia Rivera Cusicanqui (2010) and Leanne Betasamosake Simpson (KLEIN, 2012), we will question those practices and assumptions, demonstrating how these authors challenge us not only to change the usual theoretical framework naturalized in Brazilian philosophy, but, above all, to operate an ethical and political change in the relationships that we usually establish with philosophy.
Descolonizar a filosofia brasileira: desafios éticos e políticos para as filosofias do sul global
Keywords: Brazilian philosophy; Coloniality; Historiography; University practices